Efektifitas Pemakaian Berongsong terhadap Pertumbuhan dan Perkembangan Buah Jambu Air Madu Deli Hijau (Syzygium aqueum) - ., Roha; Juhan, Muhammad; Mei Arini , Silvia Fitri (Program Studi Agroteknologi, 2022)
Guava water honey (Syzygium aqueum) is an introduced fruit plant that was released as a variety of “Jabu Air Madu Deli Hijau” in 2012, but has not been widely cultivated for commercial purposes. Honey water guava comes from the guava tribal family or Myrtaceae which has 3 varieties, namely red, green and white. Now the green deli honey guava is one of the newest leading commodities which has been widely developed by horticultural farmers in the city of Binjai. This study aims to explain whether the effectiveness of brongsong affects the growth and development of green deli honey guava fruit, by obtaining good quality green deli honey guava fruit. This study used a non-factorial randomized block design (RAK), with 6 different brongsong treatments, repeated 4 times, a total of 24 research objects. The treatments studied were: R0 = Control (without berongsong), R1= Blue Plastic, R2 = Black Plastic, R3 = Red Plastic, R4 = Oil paper, R5 = Clear plastic. The data collected were analyzed by means of variance (Anova), if they were significantly different, then followed by the 5% BNT test. The results showed that brongsong in the R4=Paper oil treatment gave good results on the unit weight of the fruit, and the sugar content of the fruit. And did not give significantly different results on the parameters of fruit length, fruit diameter, fruit bunch resistance and overall fruit weight.